2007
DOI: 10.1101/gad.1516407
|View full text |Cite
|
Sign up to set email alerts
|

A new mouse model to explore the initiation, progression, and therapy of BRAFV600E-induced lung tumors

Abstract: Mutationally activated BRAF V600E (BRAF VE) is detected in ∼6% of human malignancies and promotes sustained MEK1/2-ERK1/2 pathway activation. We have designed BRaf CA mice to express normal BRaf prior to Cre-mediated recombination after which BRaf VE is expressed at physiological levels. BRaf CA mice infected with an Adenovirus expressing Cre recombinase developed benign lung tumors that only rarely progressed to adenocarcinoma. Moreover, BRaf VE -induced lung tumors were prevented by pharmacological inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
566
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(591 citation statements)
references
References 21 publications
25
566
0
Order By: Relevance
“…However, in settings unrelated to either HPV infection or deregulation of Rb, P16 ink4A has a function as a negative regulator of cell proliferation, and its expression can be linked to oncogene-induced senescence, causing irreversible growth arrest. [16][17][18][19] The induction of P16 INK4A in premalignant lesions and its loss during malignant transformation have been demonstrated in carcinogenesis of the liver, lung, and pancreas. [16][17][18][19] In the previous study, 1 P16 INK4A expression was completely lost in 50% of low-grade mucinous adenocarcinomas, and the remaining cases showed very patchy expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in settings unrelated to either HPV infection or deregulation of Rb, P16 ink4A has a function as a negative regulator of cell proliferation, and its expression can be linked to oncogene-induced senescence, causing irreversible growth arrest. [16][17][18][19] The induction of P16 INK4A in premalignant lesions and its loss during malignant transformation have been demonstrated in carcinogenesis of the liver, lung, and pancreas. [16][17][18][19] In the previous study, 1 P16 INK4A expression was completely lost in 50% of low-grade mucinous adenocarcinomas, and the remaining cases showed very patchy expression.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] The induction of P16 INK4A in premalignant lesions and its loss during malignant transformation have been demonstrated in carcinogenesis of the liver, lung, and pancreas. [16][17][18][19] In the previous study, 1 P16 INK4A expression was completely lost in 50% of low-grade mucinous adenocarcinomas, and the remaining cases showed very patchy expression. 1 In our study, P16 INK4A was specifically expressed in papillary tufts, and not in the surrounding flat mucinous epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports have now demonstrated that oncogene-induced senescence does indeed occur in vivo in human tumors and in mouse tumor models (Braig et al, 2005;Chen et al, 2005;Collado et al, 2005;Michaloglou et al, 2005;Courtois-Cox et al, 2006;Dankort et al, 2007;Sarkisian et al, 2007). Collectively, investigators have observed that mutations in K-ras, B-raf, PTEN and NF1 can trigger cellular senescence in vivo.…”
Section: History Of Oncogene-induced Senescencementioning
confidence: 99%
“…In addition to the first reported cellular senescence imposed by extensive proliferation and telomere shortening in human fibroblasts, it has become increasingly clear that genetic alterations and cellular stresses or damages linked to cancer development also trigger senescence. Animal models have suggested that preventing senescence can promote more malignant tumour progression and cells carrying characteristics of senescent cells can be found in pre-malignant samples that are lost as the state of transformation of the tumour cells increases (Braig et al, 2005;Collado et al, 2005;Dankort et al, 2007).…”
Section: P53 Isoforms Unravel P53 Functional Domainsmentioning
confidence: 99%